A Discovery Learning Model Based on Viewing Activities in Teaching News Texts - Angela, Rustiana; Ahmad Fikri Aziz Masduki; Masduki Duriyat (The Future of Education Journal, 2025)
This study aims to produce discovery model based on viewing activity (MPBKM) for learning news texts in SMP / MTs. The ability to understand news texts for students is needed to avoid misunderstandings. Learning news text at the SMP / MTs level must be presented attractively so that students like learning and accelerate in understanding the contents of the news text. The method used in this research is research and development which is carried out by analyzing the teacher's needs, the characteristics of the discovery model and the steps of viewing activities; develop models, validate, and revise; testing the feasibility of the model on SMP and MTs teachers. The research techniques used at the research stage were observation, interviews, and questionnaire analysis. The research respondents used were teachers of Indonesian language subjects in SMP and MTs in Indramayu Regency. Based on the results of the study, information was obtained that the use of discovery learning models that can increase student activity is needed. Therefore, a discovery model based on viewing activities was developed in teaching news texts for SMP / MTs students. The learning model developed has very good validity and based on SMP / MTs teachers who are experienced in teaching news texts, MPBKM has the feasibility of being used in teaching news texts to students. In addition, MPBKM can increase student activity and creativity in learning.